Design Model for the Development of Agrarian Economy: Food Aspect - Samygin, Denis Yuryevich; Baryshnikov, Nikolaj Georgievich; Mizjurkina, Ljudmila Alekseevna (Economy of Regions, 2017)
Based on the assessment of the agrarian economy development and generalization of the main directions of scientific thought, the article shows that in the last decade, the activation of agrarian policy has promoted positive shifts only in the certain directions. These shifts are not connected with a decrease in import dependence in the main food commodities. This has resulted in a low level of food self-sufficiency, seed and breeding raw materials for food production. On the example of Penza region, the authors reveal the main reasons of the low effectiveness of state measures, note their redistribution in favour of the large-scale enterprises, which cannot alone solve the import substitution problem. Using econometric methods and the Organisation for Economic Cooperation and Development (OECD) method, we have proved that the current state support mechanism is not connected with the extension of the food programme, and the subsidizing does not stimulate producers to increase the output of production. The method of statistical distribution allowed us to conclude that the problem consists in the current format of state regulation, which is implemented through financial instruments of monetary and credit institutes. Moreover, due to the low parameters of solvency and a lack of mortgage base of the most of the enterprises, it obviously deprives them of borrowed funds and budgetary provisions. On this basis, the authors draw the conclusion that a considerable part of agrarian resources in the region is not involved in the solution of food problems. We emphasize that the project management of agrarian production can become the main driver, allowing to the majority of producers to get the access to the attracted and budgetary resources. Moreover, as the received empirical model shows, the effectiveness of the operating support measures increases. The research on the basis of the theory of marginal efficiency of expenses has shown the considerable opportunities of increase in relative to a rouble of additional investments in the organizations with low financial performance providing corresponding conditions. The results of the research will be used for the development of the offers for the modernization of methods and models in strategic planning and forecasting of the development of agroindustry.